Fungal contaminants in Sicilian livestock feeds and first studies on the enzymatic activity of Aspergillus isolates - Mirabile, G.; Bella, P.; Conigliaro, G.; Giambra, S.; Alberto, M.; Davino, S.; Torta, L. (Cuban Journal of Agricultural Science, 2019)
The purposes of this study were 1) to determine the total fungal contamination in Sicilian raw materials and livestock, 2) to evaluate the occurrence of Aspergillus spp., Penicillium spp. and Fusarium spp., 3) to identify fungi belonging to the genus Aspergillus and 4) to determine their ability to produce cellulolytic enzymes. Fourteen feed samples were collected in a feed mill near to Palermo (Sicily, Italy). Analysis of the total mycobiota was performed on Sabourad Dextros Agar (SAB) and Potato Dextrose Agar (PDA) and total fungal counts were expressed as CFU/g. Aspergillus spp. isolates were selected on the basis of the frequency of isolation and identified using micro and macro-morphological characteristics and ITS sequence analysis. The ability of the Aspergillus isolates to produce cellulolytic enzymes was tested qualitatively by in vitro assay at two temperature, 25 and 30 °C, and in static and shaking condition. Total fungal population ranged from 1.11x106 to 1.31x108 and from 1.11x103 to 1.58x106 CFU/g on PDA and SAB, respectively. All feed samples showed the recurrent presence of colonies belonging mostly to the ubiquitous genera Aspergillus, Fusarium and Penicillium. Eight isolates of Aspergillus spp. were obtained and identified as A. amstelodami, A. awamori, A. flavus, A. niger, A. oryzae and A. tubingensis. Between them, A. awamori, A. niger and A. tubingensis showed the highest enzymatic activity. The presence of potential mycotoxigenic isolates of Aspergillus spp. in the analysed feeds represents a risk for animal health; moreover their ability to produce cellulolytic enzymes can seriously affect feed quality. Key words: toxygenic moulds, raw materials, animal foods, cellulolytic activity.